Răspuns :
a-b = 47
a:b= 3 rest 7 ⇒a = 3b + 7
(acum inlocuim in diferenta)
3b+7 - b = 47
2b+ 7 = 47
2b= 47-7
2b= 40
b= 40 : 2
b= 20
a= 47 + 20
a=67
PROBA:
67 - 20 = 47 CORECT!
67 : 20 = 3 rest 7 CORECT !
SUCCES !!
Daca nu intelegi ceva sa imi spui ca sa-ti explic
a:b= 3 rest 7 ⇒a = 3b + 7
(acum inlocuim in diferenta)
3b+7 - b = 47
2b+ 7 = 47
2b= 47-7
2b= 40
b= 40 : 2
b= 20
a= 47 + 20
a=67
PROBA:
67 - 20 = 47 CORECT!
67 : 20 = 3 rest 7 CORECT !
SUCCES !!
Daca nu intelegi ceva sa imi spui ca sa-ti explic